2009
DOI: 10.1243/14644193jmbd187
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear vibration signature analysis of a high-speed rotating shaft due to ball size variations and varying number of balls

Abstract: In this article, a mathematical model has been developed to predict the non-linear dynamic behaviour of a high-speed unbalanced rotating shaft due to ball size variations and varying number of balls. In the mathematical formulation, the contact between balls and inner/outer races is considered as a non-linear spring, whose stiffness is obtained using Hertzian elastic deformation theory. A detailed contact-damping model reflecting the influences of the surface profiles and the speeds of both contacting elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…Čia autoriai parašė tiesioginę judesio lygtį, judesio lygties išvedimas detaliai paaiškintas Upadhyay ir kitų (Upadhyay et al 2009) straipsnyje.…”
Section: Rotorinių Sistemų Dinamikos Tyrimų Apžvalgaunclassified
“…Čia autoriai parašė tiesioginę judesio lygtį, judesio lygties išvedimas detaliai paaiškintas Upadhyay ir kitų (Upadhyay et al 2009) straipsnyje.…”
Section: Rotorinių Sistemų Dinamikos Tyrimų Apžvalgaunclassified
“…Many researchers developed special technique on dynamic behavior considering details of geometric parameters and applicable conditions of rolling bearings. Aktürk et al [3] and Upadhyay et al [4] presented theoretical investigations of varying preload, the influence of the number of the balls, and ball diameters on vibration characteristics of a rotor bearing system. Aktürk [5] and Harsha et al [6] researched the effect of surface waviness on vibrations of ball bearings.…”
Section: Introductionsmentioning
confidence: 99%
“…However, their model demonstrated certain limitations, such as the fact that the bearings were subjected to pure axial preload only. Upadhyay et al 12 studied the vibration signature of a high-speed shaft-ball bearing system by varying the ball size and the number of balls. They concluded that symmetric combinations of off-sized balls produced vibrations equivalent to multiples of the cage frequency, while a single off-sized ball produced vibrations equivalent to the cage frequency.…”
Section: Introductionmentioning
confidence: 99%